PEMBERIAN EDUKASI TENTANG HIPERTENSI, PENCEGAHAN DAN PERAWATANYA DI KELURAHAN SUMBER AGUNG KEMILING BANDAR LAMPUNG - Sri Maryuni; Aulia Rahman; Fajar Yudha; Fitri Nurhayati (Jurnal Pengabdian Kepada Masyarakat, 2020)
Hypertension is one of the ten biggest diseases in Lampung province. Hypertension if left untreated will cause serious complications. Providing education about hypertension, its prevention and treatment is one treatment, so that it can change people's behavior towards their daily lifestyle.Health education activities in Sumber Agung Village, Kemiling, Bandar Lampung City are carried out by lecture and question and answer methods. The activity begins with a blood pressure check, then provides health education. The activity ended with an evaluation both orally and in writing.The results of the activity show that there is an effect of education on public knowledge about hypertension, both prevention and treatment. With this education, it is hoped that the community can change health behavior related to bad lifestyles for the better.